The role of the human cerebellum in representing social behavior sequences: An SDM-PSI meta-analysis - Yuting Zhang; Yidan Qiu; Shuting Lin; Xiaoyu Zheng; Liwei Tan; Xia Liu; Ruiwang Huang (NeuroImage)
Although the cerebellum has been widely considered to be a motor structure, recent studies have shown that it is also involved in constructing sequences of social events. However, little is known about (1) whether explicit sequencing processes elicit stronger cerebellar activation than non-sequencing processes, (2) whether the cerebellar sequence detection function is more applicable to social or non-social contexts, or (3) whether the cerebellum exhibits consistent or heterogeneous activation patterns in representing behavioral sequences across contexts. Thus, we conducted a meta-analysis of 13 neuroimaging studies by using a seed-based d mapping with permutation of subject images (SDM-PSI) approach. The results showed that the cerebellar Crus I and II were activated more strongly in social sequencing processes than in social non-sequencing, indicating that sequence detection is a basic function of the cerebellum. In sequencing processes, the cerebellar posterior Crus II responded more strongly to social than to non-social events, suggesting that the sequencing function of this cerebellar sub-region is more applicable to social contexts. The posterior cerebellum exhibited heterogeneous activation patterns, with distinct functional specializations in Crus I and Crus II. These findings provide a deeper understanding of the functions of the cerebellar regions in social cognition.